1977
DOI: 10.1128/jb.130.3.1333-1344.1977
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of Treponema pallidum (Nichols strain) attached to cultured mammalian cells

Abstract: This paper describes the attachment of Treponema pallidum (Nichols strain) to cultured mammalian cells as a visualized by scanning electron microscopy. Treponemes were incubated for 3 hr with cultured cells derived from normal rabbit testes or human skin epithelium, then fixed, processed with critical-point drying, and examined with a Cambridge Mark 2A scanning electron microscope. Large numbers of treponemes became attached to the cultured cells without altering the morphological integrity of the cultured cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…It has been reported that T. pallidum could attach to a series of cultured cells derived from human and other mammals. 7,9 Similar to previous studies, the attachment of treponemes did not alter the morphological integrity of HBMECs. The difference is that our results showed that attached treponemes were concentrated on certain areas of cell surface rather than evenly distributed on the cell surface.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…It has been reported that T. pallidum could attach to a series of cultured cells derived from human and other mammals. 7,9 Similar to previous studies, the attachment of treponemes did not alter the morphological integrity of HBMECs. The difference is that our results showed that attached treponemes were concentrated on certain areas of cell surface rather than evenly distributed on the cell surface.…”
supporting
confidence: 83%
“…Fitzgerald et al thought that attachment of treponemes to cultured cells appeared at a very close physical proximity. 9 However, our results showed that treponemes seemed to have merged with HBMECs at the attachment point with tips. T. pallidum was found to exist in the intercellular junctions of endothelial monolayer and was able to make its way below the monolayer.…”
mentioning
confidence: 53%
“…Numerous reports (7, 8, 14-16, 18, 19, 21) have described the interaction of T. pallidum and tissue cells and the nature of attachment as determined by electron microscopy. Fitzgerald et al (8) and Repesh et al (21) reported that T. pallidum caused no morphological changes of tissue culture cells. However, in further studies, Fitzgerald et al (15) and Oakes et al (18) described various degrees of the cultured cell disruption caused by coincubation with T. pallidum.…”
mentioning
confidence: 99%
“…THE ADHESION OF bacteria to eukaryotic cell surfaces has been studied extensively (McNeish et al 1975;Fitzgerald et al 1977) and various methods of quantitation used. McNeish, for example, determined the number of bacteria adhering to the eukaryotic cells by blending the preparation and then counting the number of micro-organisms present by conventional bacteriological tests.…”
mentioning
confidence: 99%